Vascularized Iliac Bone Graft for Complex Closure During Spinal Deformity Surgery. Issue 7 (July 2019) - Reece, Edward M.; Raghuram, Anjali C.; Bartlett, Erica L.; Lazaro, Tyler T.; North, Robert Y.; Bohl, Michael A.; Ropper, Alexander E.
Abstract : Summary: Spinal pseudarthrosis is failure of bony union across a segment where arthrodesis has been attempted. A variety of treatment approaches have been proposed to promote bony union, including use of vascularized bone graft. We report a successful application of vascularized pedicled iliac crest bone graft (ICBG) to treat recurrent lumbar and sacral pseudarthrosis. The vascularized ICBG offers the advantages of biocompatibility, mechanical stability, and minimal antigenicity. Vascularized bone transfers to the spine undergo fusion without resorption, even in the presence of compressive and rotatory forces. With its ease of access within the operative field and limited donor site morbidity, vascularized ICBG is an ideal orthobiologic that expedites time to bony union. Abstract : Supplemental Digital Content is available in the text.